Mechanisms for Recovering Libyan Smuggled Assets within Framework of the United Nations Convention against Corruption - Altoumi, Ali Makhzoum; Negasi, Mohammad Ibrahim; Laeba, Mohamad (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to shed light on the mechanisms for recovering smuggled assets which established by United Nations Convention against Corruption, as well as the extent of the success of the State of Libya in this field. Moreover, the most important obstacles that face the State of Libya. Therefore, to clarify this point, the concept of  recovering smuggled assets and its importance as well as the legal framework for the asset recovery have studied by using the inductive and analytical approach. For that, this study could clarify that the United Nations Convention played an important role in organizing that process, as it approved legal mechanisms governing it, represented in direct recovery, international cooperation in the field of confiscation, automatic international cooperation, and finally the recovery of assets. However, these mechanisms need a real commitment on the part of States parties to activate it. Furthermore, this study explains that the State of Libya has so far failed to recover its smuggled funds, for several different reasons; therefore, it should benefit from the successful experiences in this field.
Keywords: recovery of smuggled assets; United Nations Convention against Corruption